Development of Junior High School Students Civic Disposition through Innovative Civic Education Learning Strategies - Rifky Ramadhan; R. Supyan Sauri (At Turots: Jurnal Pendidikan Islam, 2026)
This research examines strategies for teaching Pancasila and Citizenship Education in developing civic disposition behaviors among junior high school students, considering various challenges such as minimal parental support, conventional teaching methods, and limitations in resources and digital skills. PPKn plays a strategic role in shaping the nation's character and personality amid phenomena of moral degradation and globalization influences. The objective of this study is to identify and analyze effective PPKn learning strategies for enhancing SMP students' civic disposition behaviors. A qualitative approach with a case study method was employed to deeply investigate the implementation of PPKn learning strategies at SMP Itikurih Hibarna Ciparay, Bandung Regency. Data were collected through interviews, observations, and documentation, with data triangulation to ensure validity. Data analysis was conducted descriptively and qualitatively using the Miles and Huberman framework, encompassing data reduction, data presentation, and drawing conclusions with verification. The findings indicate that systematic PPKn lesson planning, student-centered implementation with innovative methods such as Project-Based Learning, and evaluation based on a scientific approach are highly effective in developing students' civic dispositions. Students successfully demonstrated improvements in moral responsibility, critical thinking, discipline, and active participation. The utilization of digital school applications also played a positive role in learning management. In conclusion, comprehensive PPKn learning strategies supported by technology and oriented toward character development are proven essential in forming a young generation with Pancasila character and responsibility as citizens.